Lithium loss from pegmatites controlled by country rock temperature - Julia Neukampf; Ben S. Ellis (Nature Communications)
The sustainable energy technologies that are required to achieve net-zero carbon emissions rely on critical metals. Pegmatite deposits are one of the world’s primary sources of these critical metals, which makes understanding their formation essential.